Positive electrode for lithium ion secondary battery and lithium ion secondary battery using the same

By using a coated conductive aid with a conductive polymer on carbon materials of specific aspect ratio and content, the oxidation issues of carbon nanotubes are mitigated, leading to improved rate characteristics in high-capacity lithium ion secondary batteries.

JP2025011564APending Publication Date: 2025-01-24NISSAN MOTOR CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023113751
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing lithium ion secondary batteries with high-capacity positive electrodes do not achieve improved rate characteristics when using carbon nanotubes as conductive additives due to oxidation issues.

Method used

Incorporating a coated conductive aid with a conductive polymer on the surface of carbon materials having a predetermined aspect ratio, where the conductive polymer content is within a specific range, to form stable electron conduction paths and maintain contact integrity.

Benefits of technology

The coated conductive aid enhances electron conductivity and maintains contact stability, thereby improving rate characteristics in lithium ion secondary batteries with increased capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011564000003
    Figure 2025011564000003
  • Figure 2025011564000001
    Figure 2025011564000001
  • Figure 2025011564000002
    Figure 2025011564000002
Patent Text Reader

Abstract

To provide means for improving the rate characteristics of a high-capacity lithium-ion secondary battery.SOLUTION: A positive electrode for a lithium ion secondary battery includes a positive electrode active material and a coated conductive additive, the coated conductive additive includes a carbon material having an aspect ratio of 10 to 2000 and a conductive polymer disposed on a surface of the carbon material, and the conductive polymer content is 5 to 30 mass% relative to 100 mass% of the total amount of the carbon material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery using the same. [Background technology]

[0002] In recent years, the spread of various electric vehicles is expected to help solve environmental and energy problems. Secondary batteries have been developed as on-board power sources for driving motors, etc., which hold the key to the spread of these electric vehicles. As secondary batteries, non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries, which are expected to have high energy density and high output, have been attracting attention.

[0003] A lithium ion secondary battery (hereinafter, simply referred to as "battery") is a battery in which lithium ions are reversibly absorbed and released in the positive and negative electrodes. In general, the positive electrode of a lithium ion secondary battery has a positive electrode active material layer containing a positive electrode active material and a conductive assistant, and as the positive electrode active material, for example, a lithium-transition metal composite oxide is used. Here, Patent Document 1 discloses a technique for increasing the capacity of a lithium ion secondary battery and suppressing the deterioration of the capacity of a lithium ion secondary battery at high output by reducing the amount of conductive agent mixed in the positive electrode. Specifically, Patent Document 1 discloses the use of carbon nanotubes having a diameter of 0.5 to 10 nm and a length of 10 μm or more as a conductive assistant. According to Patent Document 1, such a configuration allows the battery to have a large capacity and high output characteristics to be obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-221672 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, according to the studies of the present inventors, it has been found that when the technology described in Patent Document 1 is used for a high-capacity positive electrode, high rate characteristics may not be obtained.

[0006] Therefore, an object of the present invention is to provide a means for improving the rate characteristics of a high-capacity lithium-ion secondary battery. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by using a coated conductive assistant in which a conductive polymer is disposed on the surface of a carbon material having a predetermined aspect ratio, and the content of the conductive polymer relative to the carbon material is a predetermined value, thereby completing the present invention.

[0008] One embodiment of the present invention is a positive electrode for a lithium ion secondary battery comprising a positive electrode active material and a coated conductive additive, the coated conductive additive comprising a carbon material having an aspect ratio of 10 to 2000 and a conductive polymer disposed on a surface of the carbon material, the content of the conductive polymer being 5 to 30 mass% relative to 100 mass% of the total amount of the carbon material. Effect of the Invention

[0009] According to the present invention, the rate characteristics of a high-capacity lithium ion secondary battery are improved. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of a stacked (flat) non-bipolar (internal parallel connection) secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] One embodiment of the present invention is a positive electrode for a lithium ion secondary battery, comprising a positive electrode active material and a coated conductive additive, the coated conductive additive comprising a carbon material having an aspect ratio of 10 to 2000 and a conductive polymer disposed on the surface of the carbon material, the content of the conductive polymer being 5 to 30 mass% relative to 100 mass% of the total amount of the carbon material. This configuration can improve the rate characteristics of a high-capacity lithium ion secondary battery.

[0012] As described above in Patent Document 1, it is known that the use of carbon nanotubes as a conductive assistant in the positive electrode active material layer of a lithium ion secondary battery increases the capacity of the battery and provides high output characteristics. On the other hand, it has been found that in batteries that are operated at a high upper limit voltage to obtain high capacity, the rate characteristics (discharge rate characteristics) are not improved even when carbon nanotubes are used.

[0013] The conductive additive has a function of forming an electronic conduction path (conductive passage) in the positive electrode active material layer. When such an electronic conduction path is formed in the positive electrode active material layer, the internal resistance of the battery is reduced, and the output characteristics at high rates can be improved. However, in a battery that is operated at a high upper limit voltage to obtain a high capacity, the positive electrode potential becomes high during charging. In this case, if carbon nanotubes are used as the conductive additive, the carbon nanotubes are prone to oxidative loss due to their low oxidation resistance, and the electronic conduction path formed by the carbon nanotubes is broken, so it is thought that the rate characteristics are not improved.

[0014] In contrast, in the positive electrode for lithium ion secondary batteries of the present invention, a coated conductive assistant in which a conductive polymer is coated on the surface of a carbon material (high aspect ratio carbon material) having a predetermined aspect ratio is used as a conductive assistant. This prevents the carbon material from coming into direct contact with an oxidizing substance, thereby suppressing the oxidative loss of the carbon material. As a result, it is believed that the electron conduction path in the positive electrode active material layer is maintained and the rate characteristics can be improved. In this case, by controlling the content of the conductive polymer within a predetermined range, the electronic conductivity of the coated conductive assistant can be ensured, and the oxidative loss of the carbon material can be suppressed even when the oxidation potential becomes high during charging.

[0015] In addition, when a conductive assistant consisting of only a carbon material is used, an electronic conduction path is formed by contact between the carbon materials that are the conductive assistants or between the carbon materials that are the conductive assistants and the positive electrode active material. However, in this case, since both the conductive assistant and the positive electrode active material are hard and difficult to deform elastically / plastically, the contact between them is almost a point contact. In contrast, in a coated conductive assistant in which a carbon material is coated with a conductive polymer, the conductive polymer is a relatively soft material that can deform elastically / plastically, so that the contact surface is large in the contact between the coated conductive assistants or between the coated conductive assistant and the positive electrode active material, and the contact surface is easily maintained. Therefore, it is presumed that even a coated conductive assistant coated with a conductive polymer that has a lower electronic conductivity than the carbon material maintains an excellent electronic conduction path formation effect.

[0016] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the claims and is not limited to the following embodiments. The dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios. In this specification, "X to Y" indicating a range means "X or more and Y or less." Furthermore, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.

[0017] FIG. 1 is a cross-sectional view that illustrates a flat (laminated) non-bipolar (internal parallel connection) secondary battery (hereinafter also simply referred to as a "laminated secondary battery") according to one embodiment of the present invention.

[0018] As shown in Fig. 1, the stacked secondary battery 10a of this embodiment has a structure in which a substantially rectangular power generating element 21, in which a charge / discharge reaction actually proceeds, is sealed inside a laminate film 29. Here, the power generating element 21 has a configuration in which a positive electrode in which a positive electrode active material layer 13 is arranged on both sides of a positive electrode collector 11', an electrolyte layer 17 made of a separator containing an electrolytic solution, and a negative electrode in which a negative electrode active material layer 15 is arranged on both sides of a negative electrode collector 12 are laminated. Specifically, the positive electrode, the electrolyte layer, and the negative electrode are laminated in this order such that one positive electrode active material layer 13 and the adjacent negative electrode active material layer 15 face each other with the electrolyte layer 17 interposed therebetween.

[0019] As a result, the positive electrode, the electrolyte layer, and the negative electrode form one unit cell layer 19. Therefore, the stacked secondary battery 10a shown in FIG. 1 can be said to have a configuration in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel. The positive electrode current collectors of the outermost layers located on both outermost layers of the power generating element 21 each have the positive electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. That is, instead of using a current collector dedicated to the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as the outermost layer current collector as it is. Also, by reversing the arrangement of the positive electrode and the negative electrode from FIG. 1, the outermost negative electrode current collector may be located on both outermost layers of the power generating element 21, and the negative electrode active material layer may be disposed on one or both sides of the outermost negative electrode current collector.

[0020] A positive electrode current collector 25 and a negative electrode current collector 27 that are electrically connected to the electrodes (positive and negative electrodes) are attached to the positive electrode current collector 11' and the negative electrode current collector 12, respectively, and are structured to be sandwiched between the ends of the laminate film 29 and led out of the laminate film 29. The positive electrode current collector 25 and the negative electrode current collector 27 may be attached to the positive electrode current collector 11' and the negative electrode current collector 12 of the electrodes by ultrasonic welding, resistance welding, or the like, respectively, via a positive electrode terminal lead and a negative electrode terminal lead (not shown) as necessary.

[0021] The main components of the stacked secondary battery according to this embodiment will be described below.

[0022] [Current collector] The current collector has a function of mediating the movement of electrons from the positive electrode active material layer and the negative electrode active material layer described later. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.

[0023] Specifically, examples of metals include aluminum, nickel, iron, stainless steel, titanium, and copper. In addition, clad materials of nickel and aluminum, clad materials of copper and aluminum, and the like may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferable from the viewpoint of electronic conductivity, battery operating potential, and the like. Also, examples of resins having electrical conductivity include resins in which a conductive filler is added to a non-conductive polymeric material.

[0024] The current collector may have a single layer structure made of a single material, or may have a laminate structure in which layers made of these materials are appropriately combined. From the viewpoint of reducing the weight of the current collector, it is preferable to include at least a conductive resin layer made of a resin having conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. Furthermore, if the positive electrode active material layer and the negative electrode active material layer described later are conductive by themselves and can perform a current collecting function, it is not necessary to use a current collector as a member separate from these electrode active material layers. In such a form, the positive electrode active material layer described later constitutes the positive electrode as it is, and the negative electrode active material layer described later constitutes the negative electrode as it is.

[0025] [Cathode active material layer] The positive electrode active material layer includes a positive electrode active material and a coating conductive assistant. The configuration of the positive electrode for a lithium ion secondary battery according to this embodiment will be described below.

[0026] (Cathode active material) The positive electrode active material has a function of releasing ions such as lithium ions during charging and absorbing ions such as lithium ions during discharging. In the positive electrode for a lithium ion secondary battery according to this embodiment, the type of the positive electrode active material is not particularly limited.

[0027] In a preferred embodiment, the positive electrode active material is of the space group R3m from the viewpoint of having a higher capacity. The positive electrode active material belonging to the space group R3m has a layered structure (layered rock salt structure) in which lithium atomic layers and transition metal atomic layers are alternately stacked. Therefore, by using such a positive electrode active material, the battery capacity of the lithium ion secondary battery can be improved.

[0028] Examples of the positive electrode active material belonging to the space group R3m include lithium-transition metal composite oxides such as LiCoO2, LiNiO2, LiMnO2, Li(Ni-Mn-Co)O2, Li(Ni-Co-Al)O2, and those in which a part of these transition metals is replaced by other elements. In some cases, two or more positive electrode active materials may be used in combination. More preferably, a composite oxide containing lithium and nickel is used, and even more preferably, Li(Ni-Mn-Co)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter, also simply referred to as "NMC composite oxide") or Li(Ni-Co-Al)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter, also simply referred to as "NCA composite oxide") is used, and particularly preferably, NMC composite oxide is used.

[0029] As described above, the NMC composite oxide and the NCA composite oxide also include composite oxides in which a part of the transition metal element is replaced by another metal element. In this case, the other elements include Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, V, Cu, Ag, Zn, etc., and are preferably Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, more preferably Al, Sn, Nb, Ti, Zr, Mg, P, Cr, and further preferably Al, Sn, Nb, Ti, Zr, Mg, from the viewpoint of improving cycle characteristics. However, the other metal elements that can replace the transition metal element of the NCA composite oxide are other than Al.

[0030] The lithium-transition metal composite oxide as the positive electrode active material has a high theoretical discharge capacity, and is therefore preferably represented by the general formula (1): Li x Ni a M b N cO2 (wherein x, a, b, c, and d satisfy 0.8 ≦ x ≦ 1.1, a + b + c = 1, 0.33 ≦ a ≦ 0.95, 0.05 ≦ b ≦ 0.67, and 0 ≦ c ≦ 0.10. M is one or more elements selected from the group consisting of Mn and Co, and N is one or more elements selected from the group consisting of Al, Sn, Nb, Ti, Zr, and Mg). Here, x represents the atomic ratio of Li, a represents the atomic ratio of Ni, b represents the atomic ratio of M, and c represents the atomic ratio of N. The composition of each element can be measured, for example, by inductively coupled plasma (ICP) optical emission spectrometry. From the viewpoint of achieving a higher discharge capacity, in the general formula (1), it is preferably 0.80 ≦ a ≦ 0.95 (that is, a high-nickel composite oxide).

[0031] In another preferred embodiment, the positive electrode for a lithium-ion secondary battery of the present invention uses, as a positive electrode active material, a lithium-transition metal composite oxide having a composition represented by the general formula (2): Li 1.5 [Ni a Co b Mn c [Li d O3 (wherein a, b, c, and d satisfy 0 < a < 1.4, 0 ≦ b < 1.4, 0 < c < 1.4, 0.1 < d ≦ 0.4, a + b + c + d = 1.5, and 1.1 ≦ a + b + c < 1.4).

[0032] The positive electrode active material having the composition represented by the general formula (2) is a layered lithium-transition metal composite oxide composed of a solid solution of electrochemically inactive layered Li2MnO3 and electrochemically active layered LiMO2 (where M is a transition metal selected from Co, Ni, and Mn). This layered lithium-transition metal composite oxide has a site that changes to a spinel structure when subjected to charging or charge-discharge in a predetermined potential range, and it is known that after the battery is completed, it is in a state having a partial spinel phase. After charge-discharge cycle treatment, this lithium-transition metal composite oxide is useful as a material capable of obtaining a large discharge capacity exceeding 200 mAh / g.

[0033] In the general formula (2) above, a represents the atomic ratio of Ni, b represents the atomic ratio of Co, c represents the atomic ratio of Mn, and d represents the atomic ratio of Li. When 0 < a < 1.4, 0 ≤ b < 1.4, 0 < c < 1.4, 0.1 < d ≤ 0.4, a + b + c + d = 1.5, and 1.1 ≤ a + b + c < 1.4 are satisfied, the structure of the solid solution can be stabilized.

[0034] As a preferred embodiment, in the general formula (2), 0.1 ≤ a ≤ 0.75, 0 ≤ b ≤ 0.6, 0.2 ≤ c ≤ 0.9, and 0.15 ≤ d ≤ 0.35. When within the above ranges, the crystal structure of the positive electrode active material can be more stabilized. Also, a positive electrode active material with high charge-discharge characteristics and a high capacity retention rate can be obtained. From the perspective of obtaining a higher energy density, in the general formula (2), it is more preferable that 0.1 ≤ a ≤ 0.4, 0 ≤ b ≤ 0.3, 0.5 ≤ c ≤ 0.9, and 0.2 ≤ d ≤ 0.3, and it is even more preferable that 0.1 ≤ a ≤ 0.4, 0.05 ≤ b ≤ 0.25, 0.6 ≤ c ≤ 0.9, and 0.2 ≤ d ≤ 0.3.

[0035] Note that the composition of each element can be measured, for example, by inductively coupled plasma (ICP) optical emission spectrometry. Also, the method for preparing the positive electrode active material having the composition represented by the general formula (2) above is not particularly limited, and conventionally known methods can be appropriately employed.

[0036] In the positive electrode for a lithium-ion secondary battery of this embodiment, it is preferable that the positive electrode active material is a positive electrode active material having the composition represented by the general formula (1) or (2) above. Since these positive electrode active materials have a high capacity, the positive electrode potential becomes higher during charging. And in the high state of charge (SOC) region, oxidizing substances such as active oxygen species are generated and the high aspect ratio carbon material is easily oxidized and decomposed. Therefore, the effects of the invention can be obtained more remarkably.

[0037] In the lithium ion secondary battery according to this embodiment, the positive electrode active material may further include a positive electrode active material other than the positive electrode active material having the composition represented by the above general formula (1) or (2). However, in this embodiment, the content of the positive electrode active material having the composition represented by the above general formula (1) or (2) in 100% by mass of the positive electrode active material is, for example, 50% by mass or more, preferably more than 50% by mass, more preferably 70% by mass or more, even more preferably 80% by mass or more, still more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.

[0038] The content of the positive electrode active material in the positive electrode active material layer (the total amount when two or more types are contained) is not particularly limited, but is preferably 60 to 99 mass%, and more preferably 80 to 95 mass%, relative to 100 mass% of the total solid content of the positive electrode active material layer.

[0039] (Coating conductive additive) The positive electrode active material layer contains, as a conductive assistant, a coated conductive assistant that includes a carbon material having an aspect ratio of 10 to 2000 and a conductive polymer disposed on the surface of the carbon material, the content of the conductive polymer being 5 to 30 mass% relative to 100 mass% of the total amount of the carbon material.

[0040] (Carbon material with aspect ratio of 10 to 2000) The carbon material preferably has carbon as its main component. Here, "mainly carbon" means that the main component is carbon, and is a concept including both "consisting only of carbon atoms" and "consisting substantially of carbon atoms." "Consisting substantially of carbon atoms" means that the inclusion of impurities of about 2 to 3 mass % or less is acceptable. Preferably, the carbon material has a carbon purity of 99.9 mass % or more. If the carbon purity is 99.9 mass % or more, an electron conduction path is formed with a small amount of carbon added, and short circuits and capacity deterioration during charging and discharging of the battery are unlikely to occur.

[0041] The aspect ratio of the carbon material is 10 to 2000. If the aspect ratio of the carbon material is less than 10, the electron conduction path in the positive electrode active material layer is not sufficiently formed, so that the electronic resistance becomes high. As a result, high rate characteristics cannot be obtained. The aspect ratio of the carbon material is preferably 30 or more, more preferably 100 or more, even more preferably 200 or more, even more preferably 500 or more, even more preferably 800 or more, and particularly preferably 1000 or more. In such a range, the rate characteristics can be further improved. On the other hand, the aspect ratio of the carbon material is 2000 or less, preferably 1500 or less, and more preferably 1200 or less. The aspect ratio of the carbon material can be determined by taking about 10 visual fields of the cross section of the positive electrode active material layer using a scanning electron microscope (SEM), measuring the fiber length / fiber diameter of the carbon material by analyzing the particle shape measurement results of the enlarged image of the carbon material, and calculating the average value. It is preferable that the coated conductive assistant coated with a conductive polymer described later also has the above aspect ratio.

[0042] The average fiber diameter of the carbon material is not particularly limited, but is preferably 1 to 200 nm, more preferably 1 to 150 nm, more preferably 1 to 100 nm, even more preferably 1 to 80 nm, and particularly preferably 10 to 50 nm. If the average fiber diameter is 1 nm or more, oxidation loss is less likely to occur, and the rate characteristics can be further improved. If the average fiber diameter is 200 nm or less, the particles of the carbon material do not become too large relative to the particle diameter of the positive electrode active material, and a good electron conduction path is easily formed, so that the effect of the present invention can be obtained more significantly. The average fiber length of the carbon material can be obtained by taking about 10 visual fields of the cross section of the positive electrode active material layer using a scanning electron microscope (SEM), measuring the fiber diameter of the carbon material by analyzing the particle shape measurement results of the enlarged image of the carbon material, and averaging the results. It is preferable that the coated conductive assistant coated with a conductive polymer described later also has the above average fiber diameter.

[0043] Examples of such carbon materials include fibrous carbon materials such as carbon nanotubes (single-walled carbon nanotubes, multi-walled carbon nanotubes, and multi-walled carbon nanotubes), carbon nanohorns, carbon nanofibers, carbon nanofilaments, carbon fibrils, vapor-grown carbon fibers, electrospun carbon fibers, polyacrylonitrile-based carbon fibers, and pitch-based carbon fibers. Of these, it is preferable to use carbon nanotubes. The above carbon materials may be used alone or in combination of two or more kinds.

[0044] (Conductive Polymer) The conductive polymer used in the present invention is not particularly limited as long as it is a polymer compound having electrical conductivity. Preferably, the conductive polymer is a π-electron conjugated polymer compound having a structure in which double bonds and single bonds are arranged alternately in the molecular structure and having a main chain with developed π-conjugation. The conductive polymer may be one which generates carriers and exhibits electrical conductivity by doping the polymer compound with an acceptor molecule called a dopant or a donor molecule. Examples of the dopant include Li + , Na + , K + , Cs + Examples of the conductive polymer include alkali metal ions such as tetraethylammonium, alkyl ammonium ions such as tetraethylammonium, halogens, Lewis acids, protons, transition metal halides, etc. The conductive polymer used in the present invention is not particularly limited, but it is preferable that the electrical conductivity of the conductive polymer film measured by the four-probe method is, for example, 10 -3 The viscosity is 0.01 S / cm or more, preferably 0.01 S / cm or more, and more preferably 0.1 S / cm or more.

[0045] The conductive polymer is not particularly limited, but may be, for example, a polymer having one or more structural units selected from the group consisting of structural units derived from substituted or unsubstituted aniline, pyrrole, thiophene, furan, benzene, phenylenevinylene, thienylenevinylene, fluorene, naphthalene, and 3,4-ethylenedioxythiophene. The substituent is not particularly limited, but may be, for example, a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, an acyl group, an alkoxycarbonyl group, a nitro group, an amino group, a sulfo group, an alkylsulfo group, a carboxy group, an alkylcarboxy group, or a hydroxy group.

[0046] The conductive polymer is not particularly limited, but for example, polyaniline, polypyrrole, polythiophene, polyfuran, poly(p-phenylene), poly(p-phenylenevinylene), poly(thienylenevinylene), polyfluorene, polynaphthylene, poly(3,4-ethylenedioxythiophene), or derivatives thereof can be mentioned. Examples of these derivatives include those having a substituent in the monomer constituting these polymer compounds. Examples of the substituent include, but are not particularly limited to, halogen atoms, alkyl groups, alkenyl groups, alkynyl groups, alkoxy groups, acyl groups, alkoxycarbonyl groups, nitro groups, amino groups, sulfo groups, alkylsulfo groups, carboxy groups, alkylcarboxy groups, and hydroxy groups.

[0047] Among them, the conductive polymer preferably includes one or more selected from the group consisting of polyaniline, polypyrrole, polythiophene, and poly(3,4-ethylenedioxythiophene) (PEDOT). In particular, the conductive polymer preferably includes one or more selected from the group consisting of polyaniline, polypyrrole, polythiophene, and poly(3,4-ethylenedioxythiophene):polystyrenesulfonic acid (PEDOT:PSS). These conductive polymers are likely to provide high electronic conductivity. In addition, they are suitable because they are resistant to high potential regions (oxidative environments) used in high-capacity positive electrodes and to active oxygen species generated from positive electrode active materials.

[0048] Polyaniline (PANI), polypyrrole (PPy), polythiophene, and PEDOT:PSS each have a repeating structure represented by the following chemical formula, and are conductive polymers.

[0049] [ka]

[0050] In the coated conductive assistant used in the positive electrode of this embodiment, the content of the conductive polymer relative to 100% by mass of the carbon material having an aspect ratio of 10 to 2000 is 5 to 30% by mass. If the content of the conductive polymer relative to 100% by mass of the carbon material is less than 5% by mass, the high aspect ratio carbon material is likely to be oxidized and lost during charging in a high capacity positive electrode, and the rate characteristic improvement effect is not sufficiently obtained. If the content exceeds 30% by mass, the electronic conductivity may decrease, and the rate characteristic may decrease. The content of the conductive polymer relative to 100% by mass of the carbon material is preferably 8 to 30% by mass, more preferably 12 to 30% by mass, and even more preferably 15 to 30% by mass. When two or more kinds of carbon materials are included, the mass of the carbon material means the total amount of these. When two or more kinds of conductive polymers are included, the mass of the conductive polymer means the total amount of these. When the conductive polymer included in the coated conductive assistant contains a dopant, the mass of the conductive polymer includes the mass of the dopant or a salt thereof.

[0051] In the coated conductive assistant used in the positive electrode of this embodiment, a conductive polymer is disposed on the surface of the carbon material having the above-mentioned predetermined aspect ratio. The conductive polymer is disposed in a state of covering preferably 50% or more, more preferably 80% or more, even more preferably 90% or more, and particularly preferably 95% or more of the surface of the carbon material. Note that other polymeric materials such as a binder described later may be further disposed on the surface of the carbon material. However, the mass ratio of the conductive polymer in the polymeric material that is coated so as to contact the surface of the carbon material is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass.

[0052] (Method of manufacturing the coated conductive assistant) The method for producing the coated conductive assistant is not particularly limited. For example, a conductive polymer is dissolved or dispersed in a solvent. A carbon material having an aspect ratio of 10 to 2000 is added thereto and stirred and mixed to prepare a dispersion liquid. Thereafter, the dispersion liquid is heated while being stirred and mixed to remove the solvent, and the obtained solid matter is further vacuum dried, so that the conductive polymer can be disposed on the surface of the carbon material.

[0053] Here, although polymer compounds having electrical conductivity are generally difficult to dissolve in solvents, for example, by introducing a substituent into the monomer constituting the polymer compound having electrical conductivity, it is possible to impart solubility in organic solvents or water. Specifically, a polythiophene derivative synthesized from poly-3-alkyl-substituted thiophene in which an alkyl group is introduced at the 3-position of thiophene can be dissolved in organic solvents such as chloroform and methylene chloride. In addition, a polythiophene derivative synthesized from poly-3-alkylsulfonic acid thiophene in which an alkylsulfonic acid is introduced at the 3-position can be water-soluble due to the sulfo group that is compatible with water, and at the same time, self-doping is possible.

[0054] Furthermore, polymers that have sulfo groups in their molecules (water-soluble polymers) that are compatible with water can be introduced as a dopant and water dispersant, making it possible to disperse polymeric compounds in water. Specifically, the monomers that make up the polymeric compound are oxidatively polymerized in an aqueous solution of the water-soluble polymer. At this time, some of the sulfo groups in the water-soluble polymer are doped into the polymeric compound, and the polymeric compound is thought to be dispersed in water. One example of this is poly(3,4-ethylenedioxythiophene):polystyrenesulfonic acid (PEDOT:PSS), which uses polystyrenesulfonic acid as a polymer with sulfo groups in its molecules and 3,4-ethylenedioxythiophene (EDOT) as a monomer that makes up the polymeric compound.

[0055] In addition, in polyaniline, emeraldine salt and emeraldine base in a semi-oxidized state are conductive and can be dissolved in a solvent such as N-methylpyrrolidone. In this embodiment, the emeraldine base of polyaniline can be preferably used.

[0056] The heating conditions when the dispersion liquid containing the conductive polymer and the carbon material is heated while being stirred and mixed cannot be unequivocally defined because they vary depending on the type of conductive polymer. For example, the mixture can be heated at a temperature of about 60 to 100°C (preferably 70 to 90°C) for about 0.5 to 8 hours to volatilize and remove the solvent, evaporating it to dryness. The product is then dried under reduced pressure to obtain a coated conductive assistant in which the conductive polymer is disposed on the surface of the carbon material. The reduced pressure conditions are not particularly limited and can be appropriately adjusted depending on the type of solvent.

[0057] In some cases, a solution containing a monomer constituting a polymer compound, a carbon material, a solvent, and a catalyst can be prepared, and the monomer can be polymerized in the solution to obtain a coated conductive assistant in which a conductive polymer is disposed on the surface of the carbon material.

[0058] For example, a heterocyclic five-membered compound such as pyrrole can be used as a raw material to carry out oxidative cationic polymerization using an oxidizing agent such as FeCl3 at the contact surface with the carbon material. In some cases, the polymer produced can be further oxidized (doped) by the action of the oxidizing agent. It is also possible to obtain a coated conductive assistant by a similar method when a monomer other than the above is used as a raw material.

[0059] As a means for confirming that the carbon material serving as the conductive assistant is coated with a conductive polymer, a method can be used in which the element distribution on the surface of a carbon material (high aspect ratio carbon material) having an aspect ratio of 10 to 2000 in the positive electrode active material layer is examined using a scanning electron microscope with an energy dispersive X-ray spectrometer (SEM-EDX) or a transmission electron microscope (TEM-EDX). If the presence of element species derived only from the conductive polymer can be confirmed on the surface of the high aspect ratio carbon material (for example, nitrogen for polyaniline or polypyrrole, or sulfur for polythiophene or PEDOT), it can be confirmed that the high aspect ratio carbon material is coated with a conductive polymer.

[0060] The content of the coated conductive assistant that can be contained in the positive electrode active material layer (the total amount when two or more types are contained) is not particularly limited, but is preferably 0.5 to 10 mass %, and more preferably 1 to 5 mass %, relative to 100 mass % of the total solid content of the positive electrode active material layer.

[0061] The positive electrode active material layer may further contain a conductive assistant other than the coated conductive assistant. Examples of such a conductive assistant include a high aspect ratio carbon material not coated with a conductive polymer, and a carbon material having an aspect ratio of less than 10, such as acetylene black, carbon black, channel black, thermal black, and Ketjen Black (registered trademark), which may be coated with a conductive polymer. Two or more of these may be used in combination. In one embodiment, the content of the conductive assistant other than the coated conductive assistant in the positive electrode active material layer is, for example, 50 mass% or less, for example, 40 mass% or less, for example, 30 mass% or less, for example, 20 mass% or less, for example, 10 mass% or less, for example, 1 mass% or less, for example, 0 mass% (i.e., no conductive assistant other than the coated conductive assistant) relative to the total amount of the conductive assistant.

[0062] The positive electrode active material layer may further contain optional components such as a binder, in addition to the positive electrode active material and the coated conductive assistant.

[0063] (Binder) The optional binder used in the positive electrode active material layer is not particularly limited, but examples thereof include the following materials: Polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (including compounds in which hydrogen atoms are replaced by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, thermoplastic polymers such as styrene-butadiene rubber (SBR), ethylene-propylene-diene copolymer, styrene-butadiene-styrene block copolymer and its hydrogenated product, styrene-isoprene-styrene block copolymer and its hydrogenated product, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene Examples of the fluororesin include vinylidene fluoride-based fluororubbers such as vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), and vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber); and epoxy resins. Among these, polyvinylidene fluoride (PVDF), polyimide, styrene-butadiene rubber, carboxymethyl cellulose, polypropylene, polytetrafluoroethylene, polyacrylonitrile, and polyamide are preferable.

[0064] The content of the binder that can be contained in the positive electrode active material layer (the total amount when two or more types are contained) is not particularly limited, but is preferably 0.5 to 10 mass % and more preferably 1 to 5 mass % with respect to the total solid content of the positive electrode active material layer.

[0065] The thickness of the positive electrode active material layer is not particularly limited, and conventionally known knowledge about batteries can be appropriately referred to. For example, the thickness of the positive electrode active material layer is usually about 1 to 1000 μm, preferably 20 to 800 μm, more preferably 30 to 500 μm, and further preferably 40 to 200 μm. The larger the thickness of the positive electrode active material layer, the more the positive electrode active material can be retained to exhibit sufficient capacity (energy density). On the other hand, the smaller the thickness of the positive electrode active material layer, the more the discharge rate characteristics can be improved.

[0066] [Negative electrode active material layer] (Negative electrode active material) The negative electrode active material has a function of releasing ions such as lithium ions during discharge and absorbing ions such as lithium ions during charge.

[0067] Examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and lithium-transition metal composite oxides (e.g., Li4Ti5O 12 ), metal materials (tin, silicon), silicon-containing alloy-based negative electrode materials (e.g., Si 60 Sn 10 Ti 30 ), lithium alloy-based negative electrode materials (for example, lithium-tin alloy, lithium-silicon alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.). In some cases, two or more types of negative electrode active materials may be used in combination. From the viewpoint of capacity and output characteristics, silicon-containing alloy-based negative electrode materials, carbon materials, lithium-transition metal composite oxides, and lithium alloy-based negative electrode materials are preferably used as the negative electrode active materials. Of course, negative electrode active materials other than those mentioned above may be used.

[0068] Average particle diameter of the negative electrode active material (D 50) is not particularly limited, but from the viewpoint of high output, The thickness is preferably 1 to 100 μm, and more preferably 1 to 20 μm.

[0069] The content of the negative electrode active material in the negative electrode active material layer is, for example, 60% by mass or more and less than 100% by mass, preferably 80% by mass or more and 99.5% by mass or less, more preferably more than 95% by mass and 99.0% by mass or less, and even more preferably 97% by mass or more and 98.5% by mass or less, based on 100% by mass of the total solid content. If the content of the negative electrode active material is within the above range, both the battery capacity and the output characteristics can be achieved.

[0070] Furthermore, the negative electrode active material layer may further contain other additives, such as a known conductive assistant and a binder similar to those described above for the positive electrode active material layer, as necessary.

[0071] The thickness of the negative electrode active material layer is not particularly limited, and the same thickness as that described above for the positive electrode active material layer can be adopted.

[0072] [Electrolyte layer] The electrolyte layer contains an electrolytic solution (liquid electrolyte) and preferably has a configuration in which a separator is impregnated with the electrolytic solution.

[0073] (electrolyte) The electrolyte has a function as a carrier of lithium ions. The electrolyte has a form in which a lithium salt is dissolved in a non-aqueous solvent. Preferably, the electrolyte is obtained by further adding a fluorine-containing carbonate to the non-aqueous solvent in which a lithium salt is dissolved.

[0074] The non-aqueous solvent is preferably one which can easily dissolve lithium salts, and examples of such non-aqueous solvents include chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and methyl ethyl carbonate (MEC); fluorine-containing chain carbonates in which some of the hydrogen atoms of these chain carbonates are substituted with fluorine atoms; ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC). fluorine-containing cyclic carbonates in which some of the hydrogen atoms of these cyclic carbonates are substituted with fluorine atoms; methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL).

[0075] In particular, from the viewpoint of further improving the rapid charging characteristics and output characteristics, it is preferable that the non-aqueous solvent contains a chain carbonate, and it is more preferable that the non-aqueous solvent contains at least one selected from the group consisting of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).

[0076] Examples of the lithium salt include Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3.

[0077] The concentration of the lithium salt in the non-aqueous solvent is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.2 mol / L.

[0078] In addition, the electrolyte preferably further contains a fluorine-containing carbonate such as a fluorine-containing cyclic carbonate or a fluorine-containing chain carbonate. By doing so, the battery can have excellent durability even when operated at a high voltage. In addition, these fluorine-containing carbonates form a protective film on the surface of the positive electrode active material, and can increase the voltage resistance of the positive electrode active material. In this case, as the fluorine-containing carbonate, fluorine-containing cyclic carbonates such as fluoroethylene carbonate (FEC), difluoroethylene carbonate, and 4-fluoropropylene carbonate; fluorine-containing chain carbonates such as ethyl trifluoromethyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, and bis(2,2,2-trifluoroethyl) carbonate can be preferably used. The content of the fluorine-containing carbonate is not particularly limited. In a preferred embodiment, the electrolyte contains a fluorine-containing carbonate, particularly fluoroethylene carbonate, in an amount of 0.5 to 10 mass% based on the total amount of the finally obtained electrolyte. This can more significantly obtain the above-mentioned effect. When the electrolytic solution contains two or more kinds of fluorine-containing carbonates, the total amount thereof is preferably within the above range.

[0079] The electrolyte may further contain additives other than the above-mentioned components. Specific examples of such compounds include ethylene carbonate, vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and 1-ethyl-2-vinylethylene carbonate. Examples of the additives include ethylene carbonate, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyl oxyethylene carbonate, methylene ethylene carbonate, and 1,1-dimethyl-2-methylene ethylene carbonate. These additives may be used alone or in combination of two or more. The amount of additive used in the electrolyte solution may be appropriately adjusted.

[0080] (Separator) The separator constituting the electrolyte layer has a function of retaining the electrolyte to ensure lithium ion conductivity between the positive electrode and the negative electrode, and also a function of acting as a partition between the positive electrode and the negative electrode.

[0081] The separator may be in the form of, for example, a porous sheet separator made of a polymer or fiber capable of absorbing and retaining the electrolyte, or a nonwoven fabric separator.

[0082] As the separator of the porous sheet made of polymer or fiber, for example, a microporous (microporous membrane) can be used. Specific forms of the porous sheet made of the polymer or fiber include, for example, polyolefins such as polyethylene (PE) and polypropylene (PP); laminates of a plurality of these laminates (for example, a laminate having a three-layer structure of PP / PE / PP), polyimide, aramid, hydrocarbon resins such as polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), glass fibers, etc., and microporous (microporous membrane) separators can be mentioned.

[0083] As the nonwoven fabric separator, conventionally known materials such as cotton, rayon, acetate, nylon, polyester; polyolefins such as PP and PE; polyimide, aramid, etc. may be used alone or in combination.

[0084] The thickness of the separator may be the same as that of the electrolyte layer, and is preferably 5 to 200 μm, and particularly preferably 10 to 100 μm.

[0085] Also, a separator in which a heat-resistant insulating layer is laminated on a porous substrate (separator with heat-resistant insulating layer) can be used as the separator. The heat-resistant insulating layer is a ceramic layer containing inorganic particles and a binder. The separator with heat-resistant insulating layer is one having high heat resistance with a melting point or thermal softening point of 150°C or higher, preferably 200°C or higher. By having a heat-resistant insulating layer, the internal stress of the separator that increases when the temperature rises is alleviated, so that a heat shrinkage suppression effect can be obtained. As a result, it is possible to prevent the induction of short circuits between the electrodes of the battery, resulting in a battery configuration in which performance deterioration due to temperature rise is unlikely to occur. In addition, by having a heat-resistant insulating layer, the mechanical strength of the separator with heat-resistant insulating layer is improved, and the separator is unlikely to break. Furthermore, due to the heat shrinkage suppression effect and high mechanical strength, the separator is unlikely to curl during the battery manufacturing process.

[0086] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a lithium ion secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 25 and the negative electrode current collector plate 27 may be made of the same material or different materials.

[0087] A lithium ion secondary battery using the positive electrode for lithium ion secondary batteries according to the present embodiment has excellent rate characteristics, and therefore the lithium ion secondary battery using the positive electrode according to the present embodiment is suitably used as a driving power source for EVs and HEVs.

[0088] Although one embodiment of the positive electrode for a lithium ion secondary battery has been described above, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.

[0089] For example, the type of battery to which the positive electrode for a lithium ion secondary battery according to the present embodiment is applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.

[0090] The following embodiments are also included within the scope of the present invention: a positive electrode for a lithium ion secondary battery according to claim 1 having the features of claim 2; a positive electrode for a lithium ion secondary battery according to claim 1 or 2 having the features of claim 3; a positive electrode for a lithium ion secondary battery according to any one of claims 1 to 3 having the features of claim 4; a positive electrode for a lithium ion secondary battery according to any one of claims 1 to 3 having the features of claim 5; and a lithium ion secondary battery comprising the positive electrode for a lithium ion secondary battery according to any one of claims 1 to 5. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.

[0092] [Example 1] <Preparation of polyaniline (PANI)-coated conductive assistant> First, single-walled carbon nanotubes (SWCNT, manufactured by Kusumoto Chemicals Co., Ltd., TUBALL (registered trademark), average fiber diameter 12 nm, aspect ratio 1010) were prepared as a conductive assistant (carbon material).

[0093] 0.25g of polyaniline (Sigma-Aldrich, emeraldine base) and 100mL of N-methyl-2-pyrrolidone were thoroughly mixed to prepare a polyaniline solution, to which 1.00g of conductive assistant was added and stirred for 2 hours. The resulting dispersion was then heated to 80°C while stirring, and N-methyl-2-pyrrolidone was evaporated to dryness, and the mixture was further vacuum dried to prepare a polyaniline-coated conductive assistant. The content of polyaniline relative to 100% by mass of the conductive assistant (carbon material) was 25% by mass.

[0094] Preparation of test cells (Preparation of positive electrode) Li as the positive electrode active material 1.5 [Ni 0.25 Co 0.1 Mn 0.85 [Li] 0.3 A lithium-transition metal composite oxide having a composition represented by the general formula (2) above, where a=0.25, b=0.1, c=0.85, d=0.3, a+b+c+d=1.5, and a+b+c=1.2, was prepared.

[0095] Next, a suitable amount of N-methyl-2-pyrrolidone (NMP) as a slurry viscosity adjusting solvent was added to the solid content consisting of 93 parts by mass of the above positive electrode active material, 3 parts by mass of the polyaniline-coated conductive assistant prepared above, and 4 parts by mass of polyvinylidene fluoride (PVdF) as a binder, and mixed to prepare a positive electrode active material slurry. Then, the obtained positive electrode active material slurry was applied to one side of an aluminum foil (thickness 20 μm) as a current collector using a doctor blade, and the coating film was dried on a hot plate at 80 ° C. for 1 hour. Then, the coating film was pressed, placed in a vacuum dryer, and dried under vacuum conditions at 130 ° C. for 8 hours to obtain a positive electrode in which a positive electrode active material layer with a porosity of 25% was formed on the current collector.

[0096] (Preparation of test cell) The prepared positive electrode was punched out to φ15 mm, and the positive electrode active material layer was placed opposite to a metallic lithium foil (φ16 mm) serving as a counter electrode, with a polypropylene separator placed between them. Next, the laminate of the positive electrode, separator, and counter electrode was placed on the bottom side of a coin cell (CR2032, material: stainless steel (SUS316)). Furthermore, a gasket was attached to maintain insulation between the electrodes, and the electrolyte was injected with a syringe. Then, a spring and a spacer were laminated, and the upper side of the coin cell was overlapped and sealed by crimping to prepare a test cell (coin cell type lithium ion secondary battery). As the electrolyte, an electrolyte obtained by dissolving LiPF61 mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 30:70) and mixing fluoroethylene carbonate (FEC) so that the amount was 1 mass% with respect to the total amount of the finally obtained electrolyte was used.

[0097] [Example 2] <Preparation of polypyrrole (PPy)-coated conductive additive> First, single-walled carbon nanotubes (SWCNT, manufactured by Kusumoto Chemicals Co., Ltd., TUBALL (registered trademark), average fiber diameter 12 nm, aspect ratio 1010) were prepared as a conductive assistant.

[0098] A beaker was filled with 2.0 g of ferric chloride hexahydrate and 30 mL of ion-exchanged water, and the mixture was mixed to prepare an aqueous solution of ferric chloride. A conductive assistant dispersion liquid, which was prepared by thoroughly dispersing and mixing 1.00 g of conductive assistant and 100 mL of ethanol, was added to the aqueous solution of ferric chloride, and after further mixing, the mixture was cooled to 5°C or lower. A pyrrole aqueous solution, which was prepared by dissolving 0.20 g of pyrrole (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 5 mL of cooled ion-exchanged water, was added to the conductive assistant dispersion liquid containing the aqueous solution of ferric chloride, and the mixture was stirred at 5°C or lower for 1 hour and then filtered. The filtered product was thoroughly washed with ion-exchanged water and ethanol, and then vacuum-dried to obtain a polypyrrole-coated conductive assistant. The content of polypyrrole relative to 100% by mass of the conductive assistant (carbon material) was 19% by mass.

[0099] Preparation of test cells A test cell of this example was produced in the same manner as in Example 1, except that the polypyrrole-coated conductive assistant prepared above was used instead of the polyaniline-coated conductive assistant.

[0100] [Example 3] 《Preparation of PEDOT:PSS coated conductive assistant》 First, single-walled carbon nanotubes (SWCNT, manufactured by Kusumoto Chemicals Co., Ltd., TUBALL (registered trademark), average fiber diameter 12 nm, aspect ratio 1010) were prepared as a conductive assistant.

[0101] 1.00g of conductive additive was added to 27.5g of 1.1 mass% PEDOT:PSS aqueous dispersion (Sigma-Aldrich) and stirred for 2 hours. The resulting dispersion was then heated to 80°C while being stirred and mixed, evaporated to dryness, and further vacuum dried to prepare a PEDOT:PSS coated conductive additive. The content of PEDOT:PSS relative to 100 mass% of the conductive additive was 29 mass%.

[0102] Preparation of test cells A test cell of this example was produced in the same manner as in Example 1, except that the PEDOT:PSS coated conductive assistant prepared above was used instead of the polyaniline coated conductive assistant.

[0103] [Example 4] A test cell of this example was produced in the same manner as in Example 1, except that the conductive assistant was changed to 3.00 g of multi-walled carbon nanotubes (MWCNT, manufactured by Sigma-Aldrich, average fiber diameter 40 nm, aspect ratio 130) in Example 1. The content of polyaniline relative to 100 mass% of the conductive assistant (carbon material) was 8 mass%.

[0104] [Example 5] A test cell of this example was produced in the same manner as in Example 2, except that the conductive assistant dispersion liquid in Example 2 was changed to a conductive assistant dispersion liquid prepared by thoroughly dispersing and mixing 1.80 g of multi-walled carbon nanotubes (MWCNT, manufactured by Sigma-Aldrich, average fiber diameter 40 nm, aspect ratio 130) and 200 mL of ethanol. The content of polypyrrole relative to 100 mass% of the conductive assistant (carbon material) was 11 mass%.

[0105] [Example 6] A test cell of this example was produced in the same manner as in Example 1, except that the conductive assistant was changed to 3.50 g of vapor grown carbon fiber (VGCF, manufactured by Showa Denko K.K., average fiber diameter 150 nm, aspect ratio 40) in Example 1. The content of polyaniline relative to 100 mass% of the conductive assistant (carbon material) was 7 mass%.

[0106] [Example 7] A test cell of this example was produced in the same manner as in Example 3, except that the conductive assistant was changed to 6.00 g of vapor grown carbon fiber (VGCF, manufactured by Showa Denko K.K., average fiber diameter 150 nm, aspect ratio 40) in Example 3. The content of PEDOT:PSS relative to 100 mass% of the conductive assistant (carbon material) was 5 mass%.

[0107] [Comparative Example 1] A test cell of this comparative example was produced in the same manner as in Example 1 described above, except that in Example 1, the step of "Preparation of polyaniline (PANI)-coated conductive additive" was not performed, and in (production of the positive electrode), single-walled carbon nanotubes (SWCNT, manufactured by Kusumoto Chemicals Co., Ltd., TUBALL (registered trademark), average fiber diameter 12 nm, aspect ratio 1010) were used instead of the polyaniline-coated conductive additive.

[0108] [Comparative Example 2] The test cell of this comparative example was prepared in the same manner as in Comparative Example 1 described above, except that multi-walled carbon nanotubes (MWCNT, manufactured by Sigma-Aldrich, average fiber diameter 40 nm, aspect ratio 130) were used instead of the single-walled carbon nanotubes in Comparative Example 1.

[0109] [Comparative Example 3] A test cell for this comparative example was prepared in the same manner as in Comparative Example 1 described above, except that vapor-grown carbon fiber (VGCF, manufactured by Showa Denko K.K., average fiber diameter 150 nm, aspect ratio 40) was used instead of the single-walled carbon nanotubes in Comparative Example 1.

[0110] [Comparative Example 4] The test cell of this comparative example was prepared in the same manner as in Comparative Example 1 described above, except that Ketjen Black (KB, manufactured by Lion Corporation, EC600JD, average primary particle diameter 30 nm, aspect ratio 4) was used instead of the single-walled carbon nanotubes in Comparative Example 1.

[0111] [Comparative Example 5] A test cell for this comparative example was prepared in the same manner as in Comparative Example 1 described above, except that acetylene black (AB, manufactured by Denka Company, Ltd., DENKA BLACK Li-400, average primary particle diameter 50 nm, aspect ratio 1) was used instead of the single-walled carbon nanotubes in Comparative Example 1.

[0112] [Comparative Example 6] A test cell of this comparative example was produced in the same manner as in Example 1, except that the conductive assistant was changed to 1.40 g of acetylene black (AB, manufactured by Denka Company, Ltd., DENKA BLACK Li-400, average primary particle size 50 nm, aspect ratio 1) in Example 1. The content of polyaniline relative to 100 mass% of the conductive assistant (carbon material) was 18 mass%.

[0113] [Comparative Example 7] A test cell of this comparative example was produced in the same manner as in Example 3, except that the conductive assistant was changed to 3.60 g of acetylene black (AB, manufactured by Denka Co., Ltd., DENKA BLACK Li-400, average primary particle size 50 nm, aspect ratio 1). The content of PEDOT:PSS relative to 100 mass% of the conductive assistant (carbon material) was 8 mass%.

[0114] [Comparative Example 8] A test cell of this comparative example was produced in the same manner as in Example 1, except that the conductive assistant was changed to 2.50 g of Ketjen Black (KB, manufactured by Lion Corporation, EC600JD, average primary particle size 30 nm, aspect ratio 4) in Example 1. The content of polyaniline relative to 100 mass% of the conductive assistant (carbon material) was 10 mass%.

[0115] [Comparative Example 9] A test cell of this comparative example was produced in the same manner as in Example 2, except that the conductive assistant dispersion liquid in Example 2 was changed to a conductive assistant dispersion liquid prepared by thoroughly dispersing and mixing 0.55 g of Ketjen Black (KB, manufactured by Lion Corporation, EC600JD, average primary particle size 30 nm, aspect ratio 4) and 90 mL of ethanol. The content of polypyrrole relative to 100 mass % of the conductive assistant (carbon material) was 34 mass %.

[0116] [Comparative Example 10] A test cell of this comparative example was produced in the same manner as in Example 1, except that the conductive assistant was changed to 12.5 g of single-walled carbon nanotubes (SWCNT, manufactured by Kusumoto Chemicals Co., Ltd., TUBALL (registered trademark), average fiber diameter 12 nm, aspect ratio 1010) in Example 1. The content of polyaniline relative to 100 mass% of the conductive assistant (carbon material) was 2 mass%.

[0117] [Comparative Example 11] A test cell of this comparative example was produced in the same manner as in Example 1, except that the conductive assistant was changed to 8.25 g of multi-walled carbon nanotubes (MWCNT, manufactured by Sigma-Aldrich, average fiber diameter 40 nm, aspect ratio 130) in Example 1. The content of polyaniline relative to 100 mass% of the conductive assistant (carbon material) was 3 mass%.

[0118] [Comparative Example 12] A test cell of this comparative example was produced in the same manner as in Example 1, except that the conductive assistant was changed to 0.65 g of vapor grown carbon fiber (VGCF, manufactured by Showa Denko K.K., aspect ratio 40, average fiber diameter: 150 nm) in Example 1. The content of polyaniline relative to 100 mass% of the conductive assistant (carbon material) was 38 mass%.

[0119] [Comparative Example 13] A test cell of this comparative example was produced in the same manner as in Example 2, except that the conductive assistant dispersion liquid in Example 2 was changed to a conductive assistant dispersion liquid prepared by thoroughly dispersing and mixing 0.45 g of vapor grown carbon fiber (VGCF, manufactured by Showa Denko K.K., aspect ratio 40, average fiber diameter: 150 nm) and 80 mL of ethanol. The content of polypyrrole relative to 100 mass% of the conductive assistant was 41 mass%.

[0120] Evaluation of test cells The rate characteristics of the test cells prepared in the above examples and comparative examples were evaluated by the following method. The following tests were performed using a charge / discharge tester (HJ-SD8, manufactured by Hokuto Denko Corporation) in a constant temperature bath set at 25°C.

[0121] (Rate characteristics) For the test cells prepared in each Example and Comparative Example, a charge-discharge test was carried out at 25°C by charging to 4.5V in CCCV mode at 0.33C rate until the cells were fully charged, discharging to 2.0V in CC mode at 0.1C rate, and discharging to 2.0V in CC mode at 2C rate after the cells were fully charged. The ratio of the discharge capacity at 2C rate to the discharge capacity at 0.1C rate was calculated, and this was taken as the 2C rate characteristic (% vs. 0.1C). The results are shown in Table 1 below.

[0122] (DC resistance (cell DCR)) For the test cells prepared in each Example and Comparative Example, the SOC was adjusted to 50%, and the cells were discharged at a rate of 0.33 C for 10 seconds while the cell open circuit voltage was stable. The cell open circuit voltage before the start of discharge and the cell voltage 10 seconds after discharge were measured, and the cell DCR (Ω cm) was calculated by dividing the cell voltage difference before and after discharge by the discharge current value. 2 ) was sought.

[0123] Cell DCR (Ω cm 2 ) = (Cell open circuit voltage before discharge (V) - Cell voltage after 10 seconds of discharge (V)) / Discharge current value (A) × Electrode area (cm 2 ) The results are shown in Table 1 below.

[0124] [Table 1]

[0125] The results shown in Table 1 show that a lithium-ion secondary battery using a coated conductive assistant in which a carbon material having a specified aspect ratio is coated with a conductive polymer and the conductive polymer content is within a specified range exhibits excellent rate characteristics even when a high-capacity positive electrode material is used. [Explanation of symbols]

[0126] 10a laminated secondary battery, 11' Positive electrode current collector 12 Negative electrode current collector 13 positive electrode active material layer, 15 negative electrode active material layer, 17 electrolyte layer, 19 cell layer, 21 Power generation elements, 25 Positive current collector (positive tab), 27 negative electrode current collector (negative electrode tab), 29 Laminating film.

Claims

1. A positive electrode for a lithium ion secondary battery comprising a positive electrode active material and a coating conductive assistant, The coated conductive assistant includes a carbon material having an aspect ratio of 10 to 2000 and a conductive polymer disposed on a surface of the carbon material, The positive electrode for a lithium ion secondary battery comprises a conductive polymer having a content of 5 to 30 mass % relative to 100 mass % of the total amount of the carbon material.

2. 2. The positive electrode for a lithium ion secondary battery according to claim 1, wherein the carbon material has an average fiber diameter of 1 to 100 nm.

3. The conductive polymer comprises one or more selected from the group consisting of polyaniline, polypyrrole, polythiophene, and poly(3,4-ethylenedioxythiophene):polystyrenesulfonic acid (PEDOT:PSS). The positive electrode for lithium ion secondary batteries according to claim 1.

4. The positive electrode active material is represented by the general formula (1): Li x Ni a M b N c O 2 (In the formula, x, a, b, c, and d satisfy 0.8≦x≦1.1, a+b+c=1, 0.33≦a≦0.95, 0.05≦b≦0.67, and 0≦c≦0.

10.

2. The positive electrode for a lithium ion secondary battery according to claim 1, having a composition represented by the formula: M is one or more elements selected from the group consisting of Mn and Co, and N is one or more elements selected from the group consisting of Al, Sn, Nb, Ti, Zr, and Mg.

5. The positive electrode active material is represented by the general formula (2): Li 1.5 [Ni a Co b Mn c [Li] d ]O 3 2. The positive electrode for a lithium ion secondary battery according to claim 1, having a composition represented by the formula: (wherein a, b, c and d satisfy the relationships: 0<a<1.4, 0≦b<1.4, 0<c<1.4, 0.1<d≦0.4, a+b+c+d=1.5, 1.1≦a+b+c<1.4).

6. A lithium ion secondary battery comprising the positive electrode for lithium ion secondary batteries according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Conductive agent for lithium ion secondary battery positive electrode and lithium ion secondary battery using the same

    JP2012221672A